3
$\begingroup$

So I have the following problem and can't seem to arrive at the official answer:

Consider the curve whose equation is $$(2-x)y^2 = x^3$$ Obtain the equations of the lines tangent to the graph of the curve at the points where $x=3/2$.

My attempt

My first thought is that you can isolate y in this equation and then have $y$ as a function of $x$ by the function $$f(x) = \sqrt{(x^3/(-x+2)^2)}$$

But when you turn the equation into a function then obviously you can't have a single $x$ with two outputs, therefore you can't have more than one line tangent to the curve at $x=3/2$. I find this confusing. You can have the equation become a function but you can still have the equation with two outputs for one x.

So I decided to just use implicit differentiation here. Then the problem boils down to finding $$y - y(3/2) = y'(3/2)(x - 3/2)$$

So after a fair amount of work you find $y(3/2)$ and $y'(3/2)$. I would share what I got but really I'd like to see if other people come up with other results.

Official answers are $$y = 3\sqrt{3}x - 3\sqrt{3}$$ and $$y = -3\sqrt{3}x + 3\sqrt{3}$$

$\endgroup$
1
  • 1
    $\begingroup$ You can turn the equation into two functions. Just take $f_1(x) = {^+}\sqrt{\cdots}$, and $f_2(x) = {^-}\sqrt{\cdots}$ $\endgroup$
    – mr_e_man
    Apr 21 '18 at 0:39
4
$\begingroup$

You are on the right track, consider

\begin{eqnarray} \frac{{\rm d}}{{\rm d}x}[(2-x)y^2] &=& \frac{{\rm d}}{{\rm d}x}[x^3] \\ (2-x)\frac{{\rm d}y^2}{{\rm d}x} -y^2 &=& 3x^2 \\ 2(2-x)y \frac{{\rm d}y}{{\rm d}x} &=& 3 x^2 \tag{1} \end{eqnarray}

From the original equation, evaluate $x=3/2$ that gives you

$$ (2 - 3/2)y^2 = (3/2)^2 ~~~\Rightarrow ~~~ y^2 = 2 (3/2)^3 = 27/4 $$

That is

$$ y_{\pm} = 3\sqrt{3}/2 \tag{2} $$

You need to evaluate these two values into equation (1), that is evaluate the pairs $(x,y) = (3/2, 3\sqrt{3}/2)$ and $(x,y) = (3/2, -3\sqrt{3}/2)$. Can you take it from here?

$\endgroup$
1
  • $\begingroup$ I could but at this particular moment i don't have any paper and pencil with me. Although by the looks of it, I think things will match correctly $\endgroup$
    – Sigma
    Apr 20 '18 at 20:39
3
$\begingroup$

Note that fo $x\ne 2$

$$(2-x)y^2 = x^3\implies y^2=\frac{x^3}{2-x}\implies 2ydy=-\frac{2(x-3)x^2}{(2-x)^2}dx \implies\frac{dy}{dx}=-\frac{2(x-3)x^2}{2y(2-x)^2}$$

and for $x=\frac32$

$$y^2=\frac{x^3}{2-x}=\frac{\frac{27}{8}}{\frac{1}{2}}=\frac{27}{4}\implies y={\pm} \frac{3\sqrt{3}}2 $$

and we obtain

  • $(x,y)=\left(\frac32,\frac{3\sqrt{3}}2\right)\implies \frac{dy}{dx}=3\sqrt 3$

  • $(x,y)=\left(\frac32,-\frac{3\sqrt{3}}2\right)\implies \frac{dy}{dx}=-3\sqrt 3$

and finally

  • $\left(y-\frac{3\sqrt{3}}2\right)=3\sqrt 3\left(x-\frac{3}2\right)\implies y=3\sqrt 3x-\frac{9\sqrt{3}}2+\frac{3\sqrt{3}}2\implies y=3\sqrt 3x-3\sqrt{3}$

  • $\left(y+\frac{3\sqrt{3}}2\right)=-3\sqrt 3\left(x-\frac{3}2\right)\implies y=-3\sqrt 3x+\frac{9\sqrt{3}}2-\frac{3\sqrt{3}}2\implies y=-3\sqrt 3x+3\sqrt{3}$

$\endgroup$
4
  • $\begingroup$ Yes I got that same result. I also found y'(3/2) and yet my answer doesn't match the official even though it's similar $\endgroup$
    – Sigma
    Apr 20 '18 at 20:36
  • $\begingroup$ @VictorS. I obtain the same result you gave $\endgroup$
    – user
    Apr 20 '18 at 20:48
  • $\begingroup$ thank you so much. when i can i'll grab my notebook and see where i screwed up. $\endgroup$
    – Sigma
    Apr 20 '18 at 21:01
  • $\begingroup$ @VictorS. Let me know, You are welcome! Bye $\endgroup$
    – user
    Apr 20 '18 at 21:02
2
$\begingroup$

If you move all of the terms to one side of the equality, you get a description of the curve as a level curve of a function $f:\mathbb R^2\to\mathbb R$. The gradient of a function is everywhere normal to its level curves, so this suggests using the point-normal form of the equation of the tangent at $(x_0,y_0)$: $$\nabla f(x_0,y_0)\cdot(x-x_0,y-y_0)=0.$$ For this problem, we have $$f(x,y) = x^3+(x-2)y^2 \\ \nabla f = \left(3x^2+y^2,2(x-2)y\right)$$ and so an equation of the tangent at $(x_0,y_0)$ is $$\left(3x_0^2+y_0^2\right)\left( x-x_0\right)+2(x_0-2)y_0(y-y_0) = 0.$$ When $x=\frac32$, $y=\pm\frac32\sqrt3$. Plug these values into the above equation and simplify, and you’ll get exactly the two Official answers.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.